The Influence of E-Book Based on Local Wisdom on the Cognitive Learning Outcomes of Science Junior High School Students Through Outing Class Method - Rahmadiningrum, Cahyani; Wulandari, Fitria Eka (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2024)
This study measures the learning outcomes of the cognitive domain to obtain accurate information about aspects of student domain ability. Cognitive learning outcomes were researched to implement science learning through outing classes using e-books based on local wisdom. This study aims to determine the effect of e-books based on local wisdom on the cognitive learning outcomes of Junior High School students. This study is a quasi-experiment in two groups, namely experimental class (E) and control Class (K), using a direct learning model with a sample of students in class 7K of 33 students and class 7I of 35 students. Data collection techniques using Pretest-Posttest Control Group Design. The study was conducted by inviting students to do outing class learning using e-books, and tests were conducted using pretest and post-test sheets. The research Instrument used consisted of cognitive questions totaling 20 multiple choice questions with data analysis using inferential statistics with a T-test (independent samples t-test) on SPSS version 26. Results research shows no significant effect on the use of e-books based on local wisdom on the classification of living things, where the learning outcomes of experimental classes with e-book treatment are higher than the control class without e-book treatment. Thus, using e-books based on local wisdom is quite influential in improving cognitive understanding and student learning outcomes.